Transformasi Gambar Menjadi Animasi: Pengaruh Media Animated Drawings With Meta Terhadap Kreativitas Anak Usia Dini - Nina Nuriya Ma’arif; Riyadlotus Sholichah; Wulan Dwi Cahyani (Atthiflah: Journal of Early Childhood Islamic Education, 2026)
Abstract: This study aimed to analyze the effect of Animated Drawings with Meta media on improving the creativity of children aged 5–6 years at TK Mekarsari Tikung Lamongan. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The participants consisted of 15 children from Group B selected through a total sampling technique. Data were collected through creativity tests, observations, interviews, and documentation. Data analysis was conducted using descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank Test. The findings revealed that the mean creativity score increased from 5.73 in the pretest to 10.40 in the posttest. The results of the Wilcoxon test showed a Z value of -3.407 with a significance value of 0.001 (p < 0.05), indicating a significant effect of the use of Animated Drawings with Meta media on children's creativity improvement. These findings suggest that interactive digital learning media can serve as an effective alternative for stimulating creativity in early childhood education.